1995
DOI: 10.1055/s-2007-979945
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Octreotide in Acromegaly on Insulin Resistance

Abstract: An important feature of acromegaly is a reduced action of insulin on hepatic gluconeogenesis and peripheral glucosal disposal. Octreotide (SMS) exerts complex effects on hormonal and metabolic regulations affecting glucose homeostasis. Eight patients with active acromegaly despite surgical intervention (age 44.8 +/- 3.5 years, BMI 27.3 +/- 1.6 kg/m2, lean body mass (LBM) 70 +/- 3.2%, blood glucose 5.24 +/- 0.26 mmol/l, HbA1c < or = 6.5%) were investigated before and after 6 months of treatment with SMS in an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 7 publications
1
14
2
Order By: Relevance
“…An improvement of insulin resistance after surgery has been already observed for 30 years (40,53,54). This seems to be an advantage over the treatment with somatostatin analogues, which may counterbalance improvement of insulin resistance by their inhibitory effect on insulin secretion (55,56). Since surgery lowered FBG and insulin resistance irrespective of the presence or absence of SAS, we speculate that reduction of GH excess rather than cure of SAS caused amelioration of glucose metabolism.…”
Section: Discussionmentioning
confidence: 66%
“…An improvement of insulin resistance after surgery has been already observed for 30 years (40,53,54). This seems to be an advantage over the treatment with somatostatin analogues, which may counterbalance improvement of insulin resistance by their inhibitory effect on insulin secretion (55,56). Since surgery lowered FBG and insulin resistance irrespective of the presence or absence of SAS, we speculate that reduction of GH excess rather than cure of SAS caused amelioration of glucose metabolism.…”
Section: Discussionmentioning
confidence: 66%
“…Both studies found that the treatment with the SA octreotide reduces IR with a slight, but significant deterioration of glucose homeostasis in the nondiabetic patients. In 1995, Breidert et al investigated eight patients' OGTT and euglycaemic clamp results before and after treatment with octreotide 300-600 mg/d with no changes for IR after treatment (12). In our cohort, b-cell function (HOMA-b) was reduced in patients on LA therapy.…”
Section: Discussionmentioning
confidence: 72%
“…Pancreatitis is rare (Neggers et al 2007). SSA suppress plasma insulin levels and were initially thought to aggravate the glucose intolerance; however, the overall effect on glucose metabolism is not clinically significant (Breidert et al 1995), probably because the effect on GH and consequently insulin resistance predominates. A meta-analysis published in 2009 confirmed that, despite the decrease of fasting insulin and possible alteration of glucose levels during OGTT, fasting plasma glucose and HbA1c do not change significantly, arguing against a clinically significant effect (Mazziotti et al 2009).…”
Section: Medical Treatmentmentioning
confidence: 99%